Molecular prevalence of multiple genetic disorders in Border collies in Japan and recommendations for genetic counselling. (August 2016) - Mizukami, K.; Yabuki, A.; Kohyama, M.; Kushida, K.; Rahman, M.M.; Uddin, M.M.; Sawa, M.; Yamato, O.
Highlights: Mutant allele frequencies of seven genetic disorders in Border collies in Japan were examined. More than half of the dogs (56%) had no mutant alleles associated with the disorders. This finding suggests that these disorders can be removed from the population through selection. Reproductive management should be performed based on selection schemes appropriate to each disorder. Abstract: Reproductive management is necessary to prevent deleterious genetic disorders in purebred dogs, but comprehensive studies aimed at prevention of multiple underlying genetic disorders in a single breed have not been performed. The aims of this study were to examine mutant allele frequencies associated with multiple genetic disorders, using Border collies as a representative breed, and to make recommendations for prevention of the disorders. Genotyping of known mutations associated with seven recessive genetic disorders was performed using PCR assays. More than half (56%) of the Border collies had no mutant alleles associated with any of the seven disorders, suggesting that these disorders can be removed from the population over several generations. Since frequencies of each mutant allele differed among disorders, reproductive management should be performed after the establishment of prevention schemes that are appropriate for each disorder, the type and specificity of genetic test available, and the effective population size in each breeding colony.